Research synthesis on the development of economy and society in Sa Kaeo province between 2012-2022 - He , Lipeng; Wiwasukh, Montree (Journal of MCU Phetchaburi Review, 2023)
The objective of this research article is to: 1) synthesize research on the development of the economy and society in Sa Kaeo province between 2012-2022, and 2) evaluate and propose strategies for the development of the economy and society in Sa Kaeo province through a systematic document analysis and synthesis. The study found that: 1) there were a total of 188 research studies that supported the development of the economy and society in Sa Kaeo province, with all 5 priority areas of the Sa Kaeo Province Development Plan (2019-2023) fully covered. These priority areas were: 1) Self-development, society, and environment with 95 studies, 2) Agriculture and agricultural products with 14 studies, 3) Tourism with 11 studies, 4) Infrastructure and management with 53 studies, and 5) Security with 16 studies, and 2) the development strategies for Sa Kaeo province from the research studies were consistent with and built upon the goals and strategies of the Sa Kaeo Province Development Plan (2019-2023)